2011
DOI: 10.1038/onc.2011.230
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a c-Jun N-terminal kinase-2-dependent signal amplification cascade that regulates c-Myc levels in ras transformation

Abstract: Ras is one of the most frequently activated oncogenes in cancer. Two mitogen-activated protein kinases (MAPKs) are important for ras transformation: extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase 2 (JNK2). Here we present a downstream signal amplification cascade that is critical for ras transformation in murine embryonic fibroblasts. This cascade is coordinated by ERK and JNK2 MAPKs, whose Rasmediated activation leads to the enhanced levels of three oncogenic transcription factors, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 62 publications
3
42
0
Order By: Relevance
“…JNK2 has also previously been implicated as the cancer-promoting isoform of the JNK family of mitogen-activated protein kinases (Mathiasen et al, 2011). CIP2A depletionelicited downregulation of JNK2 mRNA and protein levels was verified by RT-qPCR and western blot analysis, respectively (Figures 3c and d).…”
Section: Cip2a Promotes Myc-independent Transwell Migration and Jnk2 mentioning
confidence: 60%
“…JNK2 has also previously been implicated as the cancer-promoting isoform of the JNK family of mitogen-activated protein kinases (Mathiasen et al, 2011). CIP2A depletionelicited downregulation of JNK2 mRNA and protein levels was verified by RT-qPCR and western blot analysis, respectively (Figures 3c and d).…”
Section: Cip2a Promotes Myc-independent Transwell Migration and Jnk2 mentioning
confidence: 60%
“…In addition to CIP2A promoting MYC expression, MYC is also able to stimulate CIP2A mRNA and protein expression (13), establishing a positive feedback loop between these 2 human oncoproteins. The existence of the positive feedback loop between MYC and CIP2A has been verified by 2 additional studies (9,18). This bistable relationship between CIP2A and MYC may in part account for the prevalent MYC protein expression and activity in different human cancers.…”
Section: Cip2a and Mycmentioning
confidence: 81%
“…Moreover, CIP2A expression induces the transformation of JNK2 À/À mouse embryo fibroblasts (MEF), which are otherwise defective for RAS-driven transformation (9). In addition to evidence indicating that CIP2A directly promotes malignant transformation, several recent studies have shown that CIP2A inhibition in fully malignant cancer cells results in decreased cell viability and anchorage-independent growth (4,(6)(7)(8)(10)(11)(12)(13)(14)(15).…”
Section: Oncogenic Functions Of Cip2amentioning
confidence: 99%
See 2 more Smart Citations